Audit Internal Sebagai Alat Deteksi Dini Fraud Dalam Organisasi Intra Sekolah: Pengabdian - Fitrianingsih, Dwi; Khomilah, Shally (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This Community Service Program (PKM) aims to Establish a simple and sustainable internal audit system within the student organization environment at SMKN 3 Serang City, Increase student competency and awareness of fraud risks and the importance of supervision, Foster a transparent, accountable, and professional organizational culture, Become a model of good practice that can be replicated by other schools. The implementation method of this activity is designed to address the main problems faced by non-productive partners, namely students at SMKN 3 Serang City. The main focus is directed at implementing internal audit as a strategic approach to improve performance, accountability, and effectiveness of student organization management. The approach applied emphasizes managerial aspects, simple accounting, and strengthening the evaluation system. In the final stage, the implementation team together with the school reviewed the audit results and compiled recommendations for the sustainability of the internal audit system that can be implemented independently. Thus, this program not only produces a supervisory system, but also becomes a learning tool that strengthens students' character, responsibility, and professionalism in organizations.